2021
DOI: 10.52598/jpll/3/2/10
|View full text |Cite
|
Sign up to set email alerts
|

On Domain-Specific Conceptualization and Measurement of Grit in L2 Learning

Abstract: As a personality trait, second language (L2) grit—a combination of perseverance and passion for L2 learning—has recently been proposed as a meaningful predictor of learners’ motivational behavior and L2 achievement. The results of a growing body of empirical studies carried out in various L2 contexts have substantiated the power of L2 grit in predicting L2 success. In this paper, we contend that grit and its potential effects on L2 outcomes should be conceptualized and measured in a domain-specific fashion. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…In addition, they found that the perseverance of effort exhibited the strongest relation with academic achievement followed by overall grit and consistency of interest. Although it seems that the role of domain-general grit in general academic achievement is well-established, we cannot simply assume that these findings can be applied to a domain-specific language learning field ( Teimouri et al, 2021 ), which warrants research into how grit affect language learning.…”
Section: Literature Reviewmentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, they found that the perseverance of effort exhibited the strongest relation with academic achievement followed by overall grit and consistency of interest. Although it seems that the role of domain-general grit in general academic achievement is well-established, we cannot simply assume that these findings can be applied to a domain-specific language learning field ( Teimouri et al, 2021 ), which warrants research into how grit affect language learning.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Language learning is a lengthy process that needs persistence and perseverance on the part of language learners ( MacIntyre and Khajavy, 2021 ). Thus, it is reasonable to assume that grit – the passion and perseverance for long-term goals–can be an important contributor to motivational behavior and language achievement ( Teimouri et al, 2021 ). However, much recent research that examined grit using a domain-general scale has yielded inconsistent findings ( Yamashita, 2018 ; Robins, 2019, Unpublished doctoral dissertation 1 ; Khajavy, 2021 ; Liu and Wang, 2021 ; Thorsen et al, 2021 ; Khajavy and Aghaee, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations